Collaborative Selection of Authentic Audio-Visual Materials to Enhance Intercultural Competence in an Indonesian EFL Classroom - Amalia Wildani Tahir; Chairil Anwar Korompot; Muhalim Muhalim (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2026)
This qualitative descriptive study explores the collaborative process between an English teacher and a researcher in selecting authentic audio-visual materials to enhance intercultural competence among Indonesian senior high school students. Drawing on semi-structured interviews, classroom observations, and material documentation, the study examines the teacher's considerations, the dynamics of collaborative decision-making, and the characteristics of materials that support intercultural learning. The findings reveal that material selection is guided by multiple considerations, including linguistic appropriateness, cultural relevance, curriculum alignment, and student engagement potential. The collaborative process facilitated shared expertise, reflective dialogue, and pedagogically informed choices. Selected materials demonstrated authenticity, diverse cultural representation, comprehensibility, and multimodal richness. This study contributes to understanding how teacher-researcher collaboration can enhance material selection practices in EFL contexts where intercultural competence development is increasingly recognized as essential. The findings offer practical insights for EFL practitioners seeking to integrate authentic audio-visual resources that bridge language learning with intercultural awareness.